The subject and the setting: re-imagining opportunities for primary teachers’ subject knowledge development on school-based teacher education courses - Knight, Rupert (Taylor & Francis, 2017)
The landscape of teacher education is undergoing significant change in many countries and this is often associated with a move towards greater school involvement in the preparation of teachers. One aspect of teaching expertise that is particularly challenging for primary student teachers is the development of subject knowledge across a wide range of subject areas. Subject knowledge for teaching is multi-faceted and is itself linked to broader questions about curriculum and the content that should be taught. It is timely, therefore, to consider how subject knowledge development might be reconceived in a school setting and how university and school staff might work in new ways with student teachers to this end. Communities of practice theory is employed as a framework for analysing the learning environment and evaluating these future possibilities. It is argued that collaboration with peers, with their mentoring teachers and with a wider professional community is an under-exploited way of integrating facets of subject knowledge: giving this time and status through structured activities might be a particularly fruitful form of hybrid working in situ. The paper concludes by proposing four principles to underpin this sort of practice.